NZ J Ecol 2017
DOI: 10.20417/nzjecol.41.18
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of introduced mammalian predators on New Zealand’s alpine fauna

Abstract: Alpine zones are threatened globally by invasive species, hunting, and habitat loss caused by fire, anthropogenic development and climate change. These global threats are pertinent in New Zealand, with the least understood pressure being the potential impacts of introduced mammalian predators, the focus of this review. In New Zealand, alpine zones include an extensive suite of cold climate ecosystems covering c. 11% of the land mass. They support rich communities of indigenous invertebrates, lizards, fish, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
77
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(78 citation statements)
references
References 103 publications
(145 reference statements)
0
77
0
1
Order By: Relevance
“…, O'Donnell et al . ). The New Zealand Rockwren Xenicus gilviventris (hereafter Rockwren), is a small (14–20 g) alpine specialist, only found above the climatic tree line.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…, O'Donnell et al . ). The New Zealand Rockwren Xenicus gilviventris (hereafter Rockwren), is a small (14–20 g) alpine specialist, only found above the climatic tree line.…”
mentioning
confidence: 97%
“…This is based on evidence of introduced Stoats Mustela erminea and House Mice Mus musculus preying upon Rockwren eggs and nestlings (Michelsen‐Heath ) and the increasing recognition that invasive predators are widespread within the New Zealand alpine zones (O'Donnell et al . ). Despite the assumption that invasive predators are responsible for the decline of this species, the extent and effect of predation on Rockwrens has not been investigated.…”
mentioning
confidence: 97%
“…Pye et al 1999) are capable of occupying high elevation silver and mountain beech forest and alpine tussock. Ship rats live entirely in silver tussock grassland on the sub-antarctic Macquarie Island (Pye et al 1999) and recent anecdotal evidence from trapping operations suggests they are present in the New Zealand alpine zone at certain sites (O'Donnell et al 2017) which would be comparable ecologically with Mt Misery. Furthermore, male ship rats have been recorded moving distances of up to 790 m in a night in beech forest (Pryde et al 2005), so should be capable of living in the forest and commuting into the alpine zone.…”
Section: Discussionmentioning
confidence: 99%
“…A long-term study at Mt Misery ) summarised changes in the number of mouse and stoat captures across an elevational gradient in relation to beech seed production and season, between 1974 and 1993, but did not include ship rat capture results even though these data were collected. Since 1999, ship rats have been recorded as by-catch in stoat trapping operations in alpine habitats (O'Donnell et al 2017), and analyses have shown a negative relationship between ship rats and increasing elevation (Christie et al 2006). This relationship was evident at low elevation sites (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Mice had reached New Zealand on European ships by the 1820s (King 2016) and they are now present in most habitats throughout the country (Ruscoe & Murphy 2005). They prey primarily on seeds and invertebrates (Ruscoe & Murphy 2005), and sometimes also on lizards (Newman 1994;Norbury et al 2014) and the eggs and chicks of birds (Cuthbert & Hilton 2004;O'Donnell et al 2017). Biodiversity sanctuaries have been established to protect native species on the New Zealand mainland by removing invasive mammals and excluding them with mammal-resistant fences (Innes et al 2012).…”
Section: Introductionmentioning
confidence: 99%